Social jet lag and eating styles in young adults. (2nd September 2022) - Vrabec, Alison; Yuhas, Maryam; Deyo, Alexa; Kidwell, Katherine
ABSTRACT: Social jet lag refers to circadian misalignment that occurs when people shift their sleep schedules from weekdays to weekends. Social jet lag is linked with numerous negative health outcomes, with emerging research connecting social jet lag to increased consumption of unhealthy foods. Existing research has not yet examined the associations between social jet lag and eating styles (e.g., emotional eating). Emotional eating and loss of control over eating are problematic eating styles which may lead to overeating and weight gain. Conversely, intuitive eating is associated with positive health outcomes such as lower risk of obesity. The present study examined social jet lag and eating styles in a young adult sample, as emerging adulthood is an important developmental time period for establishing healthy sleep and eating habits. Results of the current study indicated that in a sample of 372 American undergraduate participants, social jet lag significantly predicted lower intuitive eating (β = −.129, p = .012) and greater emotional eating (β = .12, p = .022) when controlling for age, sex, and chronotype. It was marginally predictive of loss of control over eating (β = .102, p = .050). Sleep quantity on weekdays (not weekends) also significantly predicted intuitive eating (p = .017) and loss of control over eating (p = .044), and sleep quality significantly predicted intuitive eating (p < .001), emotional eating (p < .001), and loss of control over eating (p < .001). These findings extend our understanding of the relationship between social jet lag and eating styles in college students. Addressing social jet lag in this population is an important consideration for their cardiometabolic health and for reducing weight fluctuations.